A Thesis using Content Analysis to Examine the Relationship between Advertising Values and Beauty Types in Boots No.7 Print Advertisements - Wright, Chloe (2017)
As a prominent form of media, advertising offers a distinctive opportunity to examine how values and beauty types are constructed to portray certain beauty ideals. For this thesis, advertising values and beauty types were analysed to examine whether combined, they conveyed specific beauty ideals. The advertisements were analysed using a content analysis. This thesis uses the value framework by Pollay (1983) and the Beauty Match Up Hypothesis by Solomon, Ashmore and Congo (1992) to determine the relationship. Values form the heart of advertisements given their ability to influence consumer behaviour and beliefs. By investigating this relationship the motivations of advertisers in terms of whether they attempt to capture attainable ideals of beauty, or standardised ideals that women feel pressurised to conform to can be better understood. Findings across the longitudinal timeframe suggest that advertisers for Boots No.7 have depicted beauty ideals both realistically and unrealistically. This thesis suggests that when advertisements use ideals that pertain to values such as modernity or distinctiveness when paired with beauty types such as ‘Trendy’, the notion that women must conform to stay on trend is reinforced. In doing so, advertisers support unattainable ideals of beauty. These findings are interpreted as a possible repercussion of changes to the social construct in the latter half of the 1980s, whereby make-up was used to help women look good for themselves not for the opposite sex. In addressing the relationships between beauty types and advertising values, there is a need to consider the conceptions of the target audience as opposed to the cultural gatekeepers of the fashion and beauty industry.